2023
DOI: 10.3389/fimmu.2023.1198365
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of CTLA-4: from mechanism to autoimmune diseases

Abstract: Autoimmune diseases (ADs) are characterized by the production of autoreactive lymphocytes, immune responses to self-antigens, and inflammation in related tissues and organs. Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is majorly expressed in activated T cells and works as a critical regulator in the inflammatory response. In this review, we first describe the structure, expression, and how the signaling pathways of CTLA-4 participate in reducing effector T-cell activity and enhancing the immunomodulatory ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 185 publications
0
12
0
Order By: Relevance
“…Lastly, for some analyses, we had a moderate to low sample size. Furthermore, we included molecules such as CTLA-4 and LAG-3, which are important for optimal regulation and homeostasis of T cells within the tumor microenvironment [ 92 , 93 ]. Given our focus on oropharyngeal carcinoma, it is important to include gamma delta T cells in our future analyses since these cells defend mucosa from pathogens and maintain homeostasis for further immunoregulatory functions [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, for some analyses, we had a moderate to low sample size. Furthermore, we included molecules such as CTLA-4 and LAG-3, which are important for optimal regulation and homeostasis of T cells within the tumor microenvironment [ 92 , 93 ]. Given our focus on oropharyngeal carcinoma, it is important to include gamma delta T cells in our future analyses since these cells defend mucosa from pathogens and maintain homeostasis for further immunoregulatory functions [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abatacept (Orencia ® , Bristol Myers Squibb, Princeton, NJ, USA), (CTLA4-Ig) acts as a competitive inhibitor for CD28 situs-binding proteins, causing T-cells to become anergic. Abatacept is currently an approved therapeutic strategy in rheumatoid arthritis and autoimmune disorders [ 62 ].…”
Section: Immunologic Strategies In Vcamentioning
confidence: 99%
“…The absence of CTLA-4 disrupts Treg cell function, leading to unchecked proliferation and activation of Tconvs, which can result in autoimmune pathology ( 150 ). Researchers have shown that introducing the extracellular domain of CTLA-4 (cdCTLA-4) into mice lacking CTLA-4 fully restores Treg activity, suggesting that cdCTLA-4 is sufficient to provide inhibitory function ( 151 ). This implies that CTLA-4 function may not necessarily involve a signal transduction process.…”
Section: Co-stimulatory Moleculesmentioning
confidence: 99%